Djikstra algorithm for finding the shortest route to company addresses in industrial areas - Jamaludin Jamaludin; Didik Setiyadi; Endang Retnoningsih (Jurnal Mantik, 2023)
Electronic maps are an application that implements manual maps into a web-based system. Useful for optimizing data from manual maps into useful information. By using a geographic information system (GIS), users can search for the location of the desired company. In this research, the Dijkstra algorithm method was implemented to find the shortest path in GIS. GIS technology uses the Dijkstra algorithm to provide data information by visually displaying road location data, place locations and the shortest path from the origin to the destination location on a map. The shortest route search geographic information system displays spatial data visualization of industrial area maps that are integrated with GoogleMaps